Thermoplastic polyvinyl alcohol composition and preparation method thereof

By using a compound plasticizer of glycerol, lignin, ionic liquid and water, combined with multi-scale molecular interactions, the problem of easy precipitation of glycerol and "burning" water in thermoplastic PVA is solved, and the stability of the material is achieved and improvement of processing performance.

CN119505452APending Publication Date: 2025-02-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311077081.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, thermoplastic polyvinyl alcohol (PVA) is prone to precipitation after long-term storage, resulting in a shortening of the material storage time limit and affecting the performance of use. At the same time, moisture "burning" is prone to occur during the thermoplastic processing, resulting in poor processing. Stability and bubble defects.

Method used

Complex plasticizers, including glycerol, lignin, ionic liquid and water, are used to reduce the melting point of PVA, improve processing fluidity, and inhibit the precipitation and dissipation of glycerol and water through multi-scale molecular interactions.

Benefits of technology

The stability and processing performance of the thermoplastic PVA composition are improved, the storage time limit of the material is extended, the defects caused by the precipitation and dissipation of glycerol and water are avoided, and the appearance and use performance of the material are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of polyvinyl alcohol thermoplastic processing, and discloses a thermoplastic polyvinyl alcohol composition and a preparation method thereof, the composition contains polyvinyl alcohol and a compound plasticizer, and the content of the compound plasticizer is 28-67 parts by weight based on 100 parts by weight of polyvinyl alcohol; the compound plasticizer contains glycerol, lignin, ionic liquid and water, and the content of the lignin is 10-40 parts by weight, the content of the ionic liquid is 5-20 parts by weight and the content of the water is 10-20 parts by weight on the basis that the content of the glycerol is 100 parts by weight. The composition can reduce the melting point of the polyvinyl alcohol, improve the processing fluidity of the polyvinyl alcohol, improve the stability of a plasticizing system, inhibit migration and precipitation of micromolecules such as glycerol in the polyvinyl alcohol, and avoid the bubble defect caused by violent dissipation of water molecules in the polyvinyl alcohol in the processing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyvinyl alcohol thermoplastic processing, and in particular relates to a thermoplastic polyvinyl alcohol composition and a preparation method thereof. Background Art

[0002] Polyvinyl alcohol (PVA) is a polyhydroxy polymer that is transparent, water-soluble, high-strength, good film-forming, antistatic, and has excellent oxygen barrier properties. Therefore, it can be used as high-end packaging film, water transfer film, laundry gel film, medical water-soluble laundry bags, etc. In particular, PVA can be completely biodegraded into carbon dioxide and water under certain conditions. The application of PVA film is in line with the sustainable development strategy and has certain potential in replacing traditional polyolefin packaging materials.

[0003] However, the hydrogen bonding between PVA molecules and within PVA molecules is very strong. As a crystalline polymer, its melting point is as high as 200-240°C, which is very close to its thermal decomposition temperature, so it is difficult to process and shape by thermoplastic molding. Although PVA can form a solution in water as a water-soluble material, and then prepare PVA film by solution casting, this method has low production efficiency, high equipment cost and high energy consumption compared with thermoplastic film processing. In order to solve these problems, the current mainstream technology is to use glycerol as a plasticizer to destroy or weaken the hydrogen bonding between PVA molecules and within PVA molecules, reduce its melting point, widen its processing window, and achieve the purpose of thermoplastic processing. Glycerol is non-toxic and has a low price. It has good advantages as a PVA plasticizer. As early as 1991, it was reported in China that PVA with a degree of alcoholysis of 88 mol% of glycerol was used for thermoplastic spinning. PVA plasticized with 40% glycerol met the thermal stability standards and had good spinnability (Zhang Yueting, Guan Guihe, et al. Synthetic Fibers, 1991 (04): 24-28.). However, the glycerol molecules inside the thermoplastic PVA prepared by conventional methods tend to migrate to the surface of the material and precipitate after being left for a long time, which reduces the storage time of the thermoplastic PVA composition and affects the appearance and performance of the material.

[0004] In view of the problem that glycerol is easy to precipitate, patent document CN102391598A utilizes water and glycerol to compound to obtain aqueous plasticizer, reduces the glycerol content in the compounded plasticizer, and can suppress the precipitation of glycerol in PVA to a certain extent. However, the water in the aqueous plasticizer is prone to "boiling" phenomenon during the thermoplastic processing, resulting in instability in the processing process and bubble defects inside the material. Therefore, there is an urgent need for a method to prepare a thermoplastic PVA composition with simple formula, stable and reliable, to achieve the problem of glycerol precipitation while realizing the thermoplastic processing of PVA. Summary of the invention

[0005] In view of the above-mentioned problems existing in the prior art, the object of the present invention is to provide a thermoplastic polyvinyl alcohol composition and a preparation method thereof, which can reduce the melting point of polyvinyl alcohol, improve its processing fluidity, improve the stability of the plasticizing system, inhibit the migration and precipitation of small molecules such as glycerol in polyvinyl alcohol, and avoid bubble defects caused by the violent escape of water molecules in polyvinyl alcohol during processing through multi-scale intermolecular interactions.

[0006] The first aspect of the present invention provides a thermoplastic polyvinyl alcohol composition, which contains polyvinyl alcohol and a compound plasticizer, wherein the content of the compound plasticizer is 28 to 67 parts by weight based on 100 parts by weight of the polyvinyl alcohol;

[0007] The compound plasticizer contains glycerol, lignin, ionic liquid and water. Taking glycerol as 100 parts by weight, the content of lignin is 10-40 parts by weight, the content of ionic liquid is 5-20 parts by weight, and the content of water is 10-20 parts by weight.

[0008] The second aspect of the present invention provides a method for preparing the above-mentioned thermoplastic polyvinyl alcohol composition, the preparation method comprising:

[0009] 1) Mix the components of the compound plasticizer and stir to make the system uniform;

[0010] 2) mixing the polyvinyl alcohol and the compound plasticizer evenly and letting the mixture stand to obtain modified polyvinyl alcohol;

[0011] 3) Extruding and granulating the modified polyvinyl alcohol to obtain a thermoplastic polyvinyl alcohol composition.

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] 1. All components of the composite plasticizer in the present invention are non-toxic, harmless, safe and environmentally friendly. Glycerin and water are widely used in skin care products, lignin is a natural material of biological origin, and ionic liquid is a new type of green solvent.

[0014] 2. The present invention utilizes a composite plasticizer containing lignin, ionic liquid, glycerol and water to lower the melting point of PVA. Lignin, ionic liquid, glycerol and water can all form hydrogen bonds with PVA. Lignin is a macromolecule and the rest are small molecules. The hydrogen bond network formed by large and small molecules is more dense and stable, avoiding the escape of water and the precipitation of glycerol. At the same time, lignin and ionic liquid provide electrostatic interaction. Such multi-scale intermolecular interaction makes the plasticization effect more reliable and stable.

[0015] 3. The lignin and ionic liquid used in the present invention can inhibit the etherification or thermal degradation of PVA at high temperature to a certain extent.

[0016] 4. The lignin, ionic liquid and glycerol used in the present invention are all high-boiling point materials, which can exist stably in thermoplastic processing and have strong interactions with low-boiling point water, so that water molecules exist mainly in the form of bound water, and no bubble defects will be generated during the processing.

[0017] 5. The method for preparing a thermoplastic polyvinyl alcohol composition provided by the present invention has simple steps, low requirements on equipment, and an adjustable formula. The prepared composition can be used for processing different PVA products.

[0018] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0020] According to a first aspect of the present invention, the present invention provides a thermoplastic polyvinyl alcohol composition, the composition comprising polyvinyl alcohol and a compound plasticizer, wherein the content of the compound plasticizer is 28 to 67 parts by weight based on 100 parts by weight of the polyvinyl alcohol;

[0021] The compound plasticizer contains glycerol, lignin, ionic liquid and water. Taking glycerol as 100 parts by weight, the content of lignin is 10-40 parts by weight, the content of ionic liquid is 5-20 parts by weight, and the content of water is 10-20 parts by weight.

[0022] In the present invention, the polyvinyl alcohol can be purchased in the form of commercially available powder or granules. The degree of polymerization of the polyvinyl alcohol is 1000-2700, and the degree of alcoholysis is 88-99 mol%. The water in the present invention is deionized water.

[0023] According to the present invention, the lignin may be one of sulfonate lignin, kraft lignin, alkali lignin and organic solvent lignin.

[0024] In the present invention, the ionic liquid may be a hydroxylated imidazole ionic liquid or an amination imidazole ionic liquid.

[0025] Specifically, the hydroxylated imidazolium ionic liquid can be selected from at least one of 1-hydroxyethyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium glutamate, 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-butylimidazolium histidine, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-pentyl-3-methylimidazolium chloride, 1-octyl-3-methylimidazolium chloride, 1-octyl-3-methylimidazolium tetrafluoroborate and 1-(2-hydroxyethyl)-3-decylimidazolium bis(trifluoromethanesulfonyl)imide.

[0026] The aminated imidazolium ionic liquid can be selected from at least one of imidazole 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminopropyl-3-methylimidazolium tetrafluoroborate, 1-aminopropyl-3-methylimidazolium bromide, 1-aminoethyl-3-methylimidazolium nitrate, 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminoethyl-3-methylimidazolium hexafluorophosphate, 1-aminoethyl-3-methylimidazolium tetrafluoroborate and 1-aminoethyl-3-methylimidazolium bromide.

[0027] The present invention utilizes quaternary components such as lignin, ionic liquid, glycerol, water, etc. to perform synergistic plasticization on polyvinyl alcohol, thereby destroying the strong hydrogen bonding between polyvinyl alcohol molecules and within the molecules; the hydrogen bonding between lignin macromolecules and small molecules such as ionic liquid, glycerol, water, etc., the hydrogen bonding between macromolecules, small molecules and PVA, and the electrostatic force interaction provided by lignin and ionic liquids jointly form multi-scale molecular interactions, reduce the melting point of polyvinyl alcohol, improve its processing fluidity, improve the stability of the plasticization system, inhibit the migration and precipitation of small molecules such as glycerol in polyvinyl alcohol, and avoid bubble defects caused by the violent escape of water molecules in polyvinyl alcohol during processing.

[0028] According to a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned thermoplastic polyvinyl alcohol composition, the preparation method comprising:

[0029] 1) Mix the components of the compound plasticizer and stir to make the system uniform;

[0030] 2) mixing the polyvinyl alcohol and the compound plasticizer evenly and letting the mixture stand to obtain modified polyvinyl alcohol;

[0031] 3) Extruding and granulating the modified polyvinyl alcohol to obtain a thermoplastic polyvinyl alcohol composition.

[0032] Preferably, the stirring time in step 1) is 10 to 30 minutes.

[0033] In the present invention, the standing in step 2) is standing at 40 to 80° C. for 24 to 48 hours.

[0034] Preferably, the extrusion temperature in step 3) is 150-200°C.

[0035] In the present invention, the mixing of materials can be carried out by various mixing equipment used in the prior art, such as a high-speed mixer, a kneader, etc. Extrusion granulation can be carried out in an extrusion molding machine, through one or more die heads of a twin-screw or single-screw extruder, to extrude into wires and cut them. These are all conventional options that can be made by those skilled in the art with reference to the prior art, and will not be described in detail here.

[0036] The present invention uses multi-scale molecular interactions as the basic preparation principle, and uses lignin, ionic liquid, glycerol, and water to synergistically plasticize PVA to prepare a thermoplastic PVA composition. The process is simple and environmentally friendly, and the formula is flexible and can be freely adjusted. The present invention not only realizes the preparation of a thermoplastic polyvinyl alcohol composition, but also broadens the application field of thermoplastic polyvinyl alcohol by improving the stability of the plasticizing system.

[0037] The substances and parameters not limited in the present invention can be selected according to the existing technology and belong to the conventional technical means in this field.

[0038] The present invention will be further described below with reference to the following examples, but is not limited to these examples.

[0039] In the following examples and comparative examples, the raw materials and the methods for measuring the properties of the compositions used are as follows:

[0040] PVA1788: polyvinyl alcohol having a degree of polymerization of 1700 and a degree of alcoholysis of 88 mol % was purchased from Sichuan Vinylon Plant of Sinopec Group.

[0041] PVA2099: polyvinyl alcohol having a degree of polymerization of 2000 and a degree of alcoholysis of 99 mol % was purchased from Sinopec Great Wall Energy Chemical (Ningxia) Co., Ltd.

[0042] PVA1995: polyvinyl alcohol having a degree of polymerization of 1900 and a degree of alcoholysis of 95 mol%, was purchased from Sichuan Vinylon Plant of Sinopec Group.

[0043] PVA1997: polyvinyl alcohol having a degree of polymerization of 1900 and a degree of alcoholysis of 97 mol%, was purchased from Sichuan Vinylon Plant of Sinopec Group.

[0044] PVA1099: polyvinyl alcohol having a degree of polymerization of 1000 and a degree of alcoholysis of 99 mol % was purchased from Sinopec Great Wall Energy Chemical (Ningxia) Co., Ltd.

[0045] Glycerol: propylene glycol, analytical grade, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0046] Sulfonate lignin: industrial product, purchased from Jinan Blue Ocean Chemical Co., Ltd.

[0047] Kraft lignin: industrial product, purchased from Jinan Blue Ocean Chemical Co., Ltd.

[0048] Alkali lignin: industrial product, purchased from Jinan Blue Ocean Chemical Co., Ltd.

[0049] Organic solvent-based lignin: industrial product, purchased from Jinan Blue Ocean Chemical Co., Ltd.

[0050] Ionic liquid 1-aminopropyl-3-methylimidazolium nitrate: purity greater than 99%, purchased from Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences.

[0051] Ionic liquid 1-aminoethyl-3-methylimidazolium tetrafluoroborate: purity greater than 99%, purchased from Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences.

[0052] Ionic liquid 1-pentyl-3-methylimidazolium chloride: purity greater than 99%, purchased from Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences.

[0053] Ionic liquid 1-hydroxyethyl-3-methylimidazolium chloride: purity greater than 99%, purchased from Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences.

[0054] Ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate: purity greater than 99%, purchased from Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences.

[0055] 1. Differential Scanning Calorimetry (DSC) Analysis: The DSC8000 differential scanning calorimeter of Perkin Elmer, USA, was used for determination. The temperature was raised from 50°C to 230°C at a rate of 10°C / min under a nitrogen atmosphere. The melting point (Tm) was determined by the peak position of the melting curve.

[0056] 2. Thermogravimetric analysis (TGA): The TGA8000 thermogravimetric analyzer of Perkin Elmer Company of the United States was used for determination in air atmosphere. The temperature was raised from 40°C to 300°C at a rate of 10°C / min. The mass loss rate at 200°C and 220°C was respectively determined as W. 200 and W 220 .

[0057] Example 1

[0058] A thermoplastic polyvinyl alcohol composition, comprising PVA1788 and a compound plasticizer, wherein the content of the compound plasticizer is 28 parts by weight based on 100 parts by weight of PVA1788;

[0059] The composite plasticizer contains glycerol, sulfonate lignin, ionic liquid 1-aminopropyl-3-methylimidazole nitrate and water. Based on 100 parts by weight of glycerol, the content of lignin is 10 parts by weight, the content of the ionic liquid is 5 parts by weight, and the content of water is 10 parts by weight.

[0060] The preparation method of the thermoplastic polyvinyl alcohol composition comprises:

[0061] 1) Mix the components of the compound plasticizer and stir for 10 minutes to make the system uniform;

[0062] 2) PVA1788 and the compound plasticizer are mixed and stirred evenly with a high-speed stirrer, and then allowed to stand at 80° C. for 24 hours to obtain modified polyvinyl alcohol;

[0063] 3) The modified polyvinyl alcohol is extruded by a single screw extruder at a temperature of 200° C. and granulated to obtain a thermoplastic polyvinyl alcohol composition.

[0064] The prepared thermoplastic polyvinyl alcohol composition can be processed and formed at a temperature of 190-210° C. The performance test results of the composition are shown in Table 1.

[0065] Example 2

[0066] A thermoplastic polyvinyl alcohol composition, comprising PVA2099 and a compound plasticizer, wherein the content of the compound plasticizer is 67 parts by weight based on 100 parts by weight of the PVA2099;

[0067] The composite plasticizer contains glycerol, sulfate lignin, ionic liquid 1-aminoethyl-3-methylimidazolium tetrafluoroborate and water. Based on 100 parts by weight of glycerol, the content of sulfate lignin is 40 parts by weight, the content of ionic liquid 1-aminoethyl-3-methylimidazolium tetrafluoroborate is 20 parts by weight, and the content of water is 15 parts by weight.

[0068] The preparation method of the thermoplastic polyvinyl alcohol composition comprises:

[0069] 1) Mix the components of the compound plasticizer and stir for 30 minutes to make the system uniform;

[0070] 2) PVA2099 and the compound plasticizer were mixed and stirred evenly with a high-speed stirrer, and then allowed to stand at 60° C. for 48 hours to obtain modified polyvinyl alcohol;

[0071] 3) The modified polyvinyl alcohol is extruded by a single screw extruder at a temperature of 180° C. and granulated to obtain a thermoplastic polyvinyl alcohol composition.

[0072] The prepared thermoplastic PVA composition can be processed and molded at a temperature of 170-190° C. The performance test results of the composition are shown in Table 1.

[0073] Example 3

[0074] A thermoplastic polyvinyl alcohol composition, comprising PVA1995 and a compound plasticizer, wherein the content of the compound plasticizer is 45 parts by weight based on 100 parts by weight of the PVA1995;

[0075] The composite plasticizer contains glycerol, alkali lignin, ionic liquid 1-pentyl-3-methylimidazolium chloride and water. Based on 100 parts by weight of glycerol, the content of alkali lignin is 20 parts by weight, the content of ionic liquid 1-pentyl-3-methylimidazolium chloride is 10 parts by weight, and the content of water is 20 parts by weight.

[0076] The preparation method of the thermoplastic polyvinyl alcohol composition comprises:

[0077] 1) Mix the components of the compound plasticizer and stir for 20 minutes to make the system uniform;

[0078] 2) PVA1995 and the compound plasticizer were mixed and stirred evenly with a high-speed stirrer, and then allowed to stand at 40° C. for 36 hours to obtain modified polyvinyl alcohol;

[0079] 3) The modified polyvinyl alcohol is extruded by a single screw extruder at a temperature of 170° C. and granulated to obtain a thermoplastic polyvinyl alcohol composition.

[0080] The prepared thermoplastic PVA composition can be processed and molded at a temperature of 160-180° C. The performance test results of the composition are shown in Table 1.

[0081] Example 4

[0082] A thermoplastic polyvinyl alcohol composition, comprising PVA1997 and a compound plasticizer, wherein the content of the compound plasticizer is 58 parts by weight based on 100 parts by weight of PVA1997;

[0083] The composite plasticizer contains glycerol, organic solvent-type lignin, ionic liquid 1-hydroxyethyl-3-methylimidazolium chloride and water. Based on 100 parts by weight of glycerol, the content of the organic solvent-type lignin is 30 parts by weight, the content of the ionic liquid 1-hydroxyethyl-3-methylimidazolium chloride is 15 parts by weight, and the content of water is 15 parts by weight.

[0084] The preparation method of the thermoplastic polyvinyl alcohol composition comprises:

[0085] 1) Mix the components of the compound plasticizer and stir for 15 minutes to make the system uniform;

[0086] 2) PVA1997 and the compound plasticizer are mixed and stirred evenly with a high-speed stirrer, and then allowed to stand at 40° C. for 48 hours to obtain modified polyvinyl alcohol;

[0087] 3) The modified polyvinyl alcohol is extruded by a single screw extruder at a temperature of 150° C. and granulated to obtain a thermoplastic polyvinyl alcohol composition.

[0088] The prepared thermoplastic PVA composition can be processed and molded at a temperature of 150-160° C. The performance test results of the composition are shown in Table 1.

[0089] Example 5

[0090] A thermoplastic polyvinyl alcohol composition, comprising PVA1099 and a compound plasticizer, wherein the content of the compound plasticizer is 28 parts by weight based on 100 parts by weight of PVA1099;

[0091] The composite plasticizer contains glycerol, sulfonate lignin, ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate and water. Based on 100 parts by weight of glycerol, the content of sulfonate lignin is 15 parts by weight, the content of ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate is 20 parts by weight, and the content of water is 10 parts by weight.

[0092] The preparation method of the thermoplastic polyvinyl alcohol composition comprises:

[0093] 1) Mix the components of the compound plasticizer and stir for 10 minutes to make the system uniform;

[0094] 2) PVA1099 and the compound plasticizer were mixed and stirred evenly with a high-speed stirrer, and then allowed to stand at 80° C. for 24 hours to obtain modified polyvinyl alcohol;

[0095] 3) The modified polyvinyl alcohol is extruded by a single screw extruder at a temperature of 190° C. and granulated to obtain a thermoplastic polyvinyl alcohol composition.

[0096] The prepared thermoplastic PVA composition can be processed and molded at a temperature of 180-200° C. The performance test results of the composition are shown in Table 1.

[0097] Comparative Example 1

[0098] Same as Example 1, except that the compound plasticizer does not contain sulfonate lignin. The performance test results of the composition are shown in Table 1.

[0099] Comparative Example 2

[0100] The same as Example 1, except that the compound plasticizer does not contain ionic liquid 1-aminopropyl-3-methylimidazole nitrate. The performance test results of the composition are shown in Table 1.

[0101] Comparative Example 3

[0102] Same as Example 1, except that the compounded plasticizer does not contain glycerol. The performance test results of the composition are shown in Table 1.

[0103] Comparative Example 4

[0104] Same as Example 1, except that the compounded plasticizer does not contain water. The performance test results of the composition are shown in Table 1.

[0105] Table 1

[0106] Tm(℃) <![CDATA[W 200 (%)]]> <![CDATA[W 220 (%)]]> Example 1 155 7.8 13.5 Example 2 161 10.8 17.4 Example 3 163 8.8 15.1 Example 4 157 10.3 15.6 Example 5 163 8.3 13.9 Comparative Example 1 165 13.2 18.9 Comparative Example 2 168 13.5 18.5 Comparative Example 3 165 17.5 20.1 Comparative Example 4 170 12.8 18.1

[0107] It can be seen from the results of the embodiments and comparative examples that the components of the compound plasticizer in the present invention act synergistically, so that the melting point of the PVA composition is greatly reduced, the processing temperature thereof is lowered, and the escape and loss of the plasticizer at high temperatures are greatly reduced, the processing flow properties at high temperatures are improved, and product defects caused by the escape of small molecules at high temperatures can be avoided.

[0108] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A thermoplastic polyvinyl alcohol composition, characterized in that The composition contains polyvinyl alcohol and a compound plasticizer, wherein the content of the compound plasticizer is 28 to 67 parts by weight based on 100 parts by weight of the polyvinyl alcohol; The compound plasticizer contains glycerol, lignin, ionic liquid and water. Taking glycerol as 100 parts by weight, the content of lignin is 10-40 parts by weight, the content of ionic liquid is 5-20 parts by weight, and the content of water is 10-20 parts by weight.

2. The thermoplastic polyvinyl alcohol composition according to claim 1, wherein The degree of polymerization of the polyvinyl alcohol is 1000-2700, and the degree of alcoholysis is 88-99 mol%.

3. The thermoplastic polyvinyl alcohol composition according to claim 1, wherein The lignin is one of sulfonate lignin, sulfate lignin, alkali lignin and organic solvent lignin.

4. The thermoplastic polyvinyl alcohol composition according to claim 1, wherein The ionic liquid is a hydroxylated imidazole ionic liquid or an amination imidazole ionic liquid.

5. The thermoplastic polyvinyl alcohol composition according to claim 4, wherein The hydroxylated imidazolium ionic liquid is selected from at least one of 1-hydroxyethyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-methylimidazolium glutamate, 1-hydroxyethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium chloride, 1-hydroxyethyl-3-butylimidazolium histidine, 1-butyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-pentyl-3-methylimidazolium chloride, 1-octyl-3-methylimidazolium chloride, 1-octyl-3-methylimidazolium tetrafluoroborate and 1-(2-hydroxyethyl)-3-decylimidazolium bis(trifluoromethanesulfonyl)imide.

6. The thermoplastic polyvinyl alcohol composition according to claim 4, wherein The aminated imidazolium ionic liquid is selected from at least one of 1-aminopropyl-3-methylimidazolium nitrate, 1-aminopropyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminopropyl-3-methylimidazolium tetrafluoroborate, 1-aminopropyl-3-methylimidazolium bromide, 1-aminoethyl-3-methylimidazolium nitrate, 1-aminoethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-aminoethyl-3-methylimidazolium hexafluorophosphate, 1-aminoethyl-3-methylimidazolium tetrafluoroborate and 1-aminoethyl-3-methylimidazolium bromide.

7. The method for preparing the thermoplastic polyvinyl alcohol composition according to any one of claims 1 to 6, characterized in that: The preparation method comprises: 1) Mix the components of the compound plasticizer and stir to make the system uniform; 2) mixing the polyvinyl alcohol and the compound plasticizer evenly and letting the mixture stand to obtain modified polyvinyl alcohol; 3) Extruding and granulating the modified polyvinyl alcohol to obtain a thermoplastic polyvinyl alcohol composition.

8. The method for preparing the thermoplastic polyvinyl alcohol composition according to claim 7, wherein: The stirring time in step 1) is 10 to 30 minutes.

9. The method for preparing a thermoplastic polyvinyl alcohol composition according to claim 7, wherein: The standing in step 2) is standing at 40 to 80° C. for 24 to 48 hours.

10. The method for preparing a thermoplastic polyvinyl alcohol composition according to claim 7, wherein: The extrusion temperature in step 3) is 150-200°C.

Citation Information

Patent Citations

  • Polyvinyl alcohol material and production method thereof

    CN102391598A

  • Ionic liquids for solubilizing polymers

    CN101522985A

  • Thermal plastic processing available polyvinyl alcohol resin, as well as preparation method and application thereof

    CN106832705A

  • Thermoplastic lignin material and preparation method thereof

    CN109608895A

  • Lignin synergistically plasticized polyvinyl alcohol and melting processing method thereof

    CN114539696A